2007
DOI: 10.1021/jo071051i
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable β-Selectivity in the Synthesis of β-1-C-Arylglucosides:  Stereoselective Reduction of Acetyl-Protected Methyl 1-C-Arylglucosides without Acetoxy-Group Participation

Abstract: An efficient and practical process to generate beta-C-arylglucoside derivatives was achieved. The process described involves Lewis acid mediated ionic reduction of a peracetylated 1-C-aryl methyl glucoside derived from the addition of an aryl-Li to selectively protected delta-D-gluconolactone. The reduction of the 2-acetoxy-1-C-oxacarbenium ion intermediates proceeds with a high degree of selectivity to give beta-C-arylglucosides without 2-acetoxy group participation. Furthermore, during the reduction process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 28 publications
1
18
0
1
Order By: Relevance
“…The molecule itself was known since 1835 and is a naturally occurring compound isolated from the bark of pear, apple, cherry, and other fruit trees . This compound was superseded by better and more selective synthetic analogs like canagliflozin,, dapagliflozin, and empagliflozin (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…The molecule itself was known since 1835 and is a naturally occurring compound isolated from the bark of pear, apple, cherry, and other fruit trees . This compound was superseded by better and more selective synthetic analogs like canagliflozin,, dapagliflozin, and empagliflozin (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the diastereoselectivity of Lewis acid-mediated silane reductions of tetra-O-protected glycopyranosides to β- C -glucosides varies from moderate to high. , Studies have shown that the stereoselectivity of the reduction step might be affected by the use of bulky reducing agents such as i -Pr 3 SiH (TIPS-H) or (TMS) 3 SiH, , conformationally restricted substrates, or other factors such as the nature of the Lewis acid ,, and the aglycone …”
Section: General Aspects Of the Synthesis Of Sglt2 Inhibitorsmentioning
confidence: 99%
“…The current synthetic route portrayed in Scheme 5.2 was the result of many process improvements over the initial route [25,26]. In the original route benzyl ether protecting groups were employed throughout the synthesis and were removed by hydrogenolysis in the final step.…”
Section: Synthetic Routementioning
confidence: 99%
“…To ascertain if only the spatial presentation of the sugar and benzyl moieties of 20 was conducive to high SGLT2 potency, alternative presentations were systematically evaluated [25]. The assumption was that high affinity SGLT2 antagonists required the distal aryl ring to bear a lipophilic substituent properly oriented so that the substituent would extend into a favorable binding pocket.…”
Section: Early Sar Of C-glucoside Based Sglt2 Inhibitorsmentioning
confidence: 99%